Razón «débil» y Educación «light» - Gervilla Castillo, Enrique (Teoría de la Educación. Revista Interuniversitaria, 2009)
The «strong» reason, which characterises the theocentric and anthropological philosophical systems of the middle ages and modernity, has been broken faced with the «un-reason» seen in the disasters of manking: war, hunger, armaments, social inequality... In consequence «weak» reason which belongs to the postmodernity is now prevalent in a large part of our society. Ontological fragmentation and «weak» thought have engendered a new way of living whose influence is seen in education which is based on relativism and individualism. The causes of this change and its positive and negative aspects are critically analyzed in this article.